Integration of the internal Supply Chain Management (SCM) towards long run competitiveness / Tengku Nurul Aishah Tengku Aziz - Tengku Aziz, Tengku Nurul Aishah (2014)
Malaysia manufacturing sector has become the major production of import and export activities where E&E sector has been identified as the largest contributor on GOP performance. In today's environment, technology is changing at a faster pace where competition among the industry players have become more intense in becoming competitive. With the new implementation of strategies and agenda by the Malaysian government, manufacturing which focus on electrical and electronics (E&E) and logistics have been one of the targeted industries which have high potential in driving Malaysia towards becoming a high income nation by 2020. As logistics has become the new targeted area, by looking through SCM there was limited studies focused on the SCM components where this area has been seen important nowadays. There are two major components of SCM which are the internal and external component. However, the internal component of SCM has been given less attention. Four objectives highlighted in this study which are providing an overview of Malaysia's manufacturing industry of E&E sector, identifying the internal SCM factors which contribute towards long run competitiveness, identifying the relationship among the internal SCM factors, and determine the influence of the internal factors towards long run competitiveness. The respondents have been selected from FMM directory 201 1 where 192 population of E&E companies involves and about 63 sample size has been used. These selected companies had gone through several stages of the data collection. They had been interviewed face to face and answered the questionnaire which had been constructed by referring to the previous studies directly, emailed and through phone calls. Throughout this study, knowledge has been identified to be significant and has direct relationship towards long run competitiveness. As for the others which are technology, communication, leadership, time, and commitment have insignificant results and does not have direct relationship with long run competitiveness. However, these internal factors of SCM do have relationships among them where good integration apply plays a crucial role in strengthen and creates a good relationships especially for the organization in becoming more effective and efficient. Furthermore, results of this study may help in giving a holistic view of the current situations which need to be seen by applying new strategies and approach to achieve long run competitiveness.